Green Customer Value, Green Brand Positioning, Environmental Knowledge, Emotional Satisfaction, Government Policies, Affecting Green Purchase Intention; Mediating Attitude Toward Green Brand - Nasyah Amanda; Immanuel Zai (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The aim of this research is to evaluate the effects of green customer value, green brand positioning, environmental knowledge, emotional satisfaction, government policies on green purchase intention. And the role of attitude toward green brand which is a mediating variable in this research. This research was conducted in Batam City, Indonesia among diffrent age groups using primary data, namely questionnaires with a total of 290 respondents. The data collection technique used in this research is based on questionnaire technique. SmartPls 3 is used as the analysis technology